Multiple intelligences in an educational context: culturally based abilities and aptitudes in the body-mind binomial - Morgado, Elsa Maria Gabriel (2024)
Objective: The aim of this study is to demonstrate that traditional education, based on psychometric theory, utilizes standardized tests that lead to dissatisfaction due to their selective and exclusionary nature. Meanwhile, the Theory of Multiple Intelligences challenges this approach, contending that standardization benefits some students while harming others. Theoretical Framework: We brought together reference authors in the specific area, as well as others who, through more recent research, have developed studies in educational, cultural and artistic activity in the community, in the area of the arts, culture and their relationship in this field of education, with a direct focus on the universe of the intelligences measured, to be enhanced and reinforced. Method: The methodology adopted for this research comprises a quantitative-qualitative and descriptive study, using a questionnaire (Multiple Intelligences Inventory - MII) with closed questions, developed in a group of schools in the North of Portugal, in which students (n=120) from the different types of education participated: regular, professional and programme for inclusion and citizenship. Results and Discussion: The results showed that the most developed multiple intelligences are Bodily-Kinesthetic and the least developed is Logical-Mathematical learning. Research Implications: The practical and theoretical implications of this research are diverse; among them, the existence of multiple intelligences that manifest themselves equally stands out. The implications include the use of this data for future research in the field of educational intervention for professionals in various areas, mainly in stimulating and reinforcing these indicators and results. Originality/Value: This research is of particular importance as it provides educators and professionals, both in initial training (higher education) and future teachers, as well as for professionals already in the field and educational universes, to intervene in an informed, appropriate and conscious manner in these areas.